Triggering of Parkin Mitochondrial Translocation in Mitophagy: Implications for Liver Diseases - Eid, Nabil; Ito, Yuko; Otsuki, Yoshinori (Frontiers in Pharmacology, 2016)
A growing body of evidence based on in vitro studies indicates that mitophagy (selective autophagic clearance of damaged mitochondria) is a prosurvival mechanism associated with cellular exposure to various mitochondrial stressors. Very recently, a limited number of publications on animal-based models of alcoholic fatty liver diseases have reported that Parkin-mediated mitophagy may mitigate hepatocyte apoptosis, improve mitochondrial quality and suppress steatosis (lipid accumulation). From this perspective, the authors focus on the mechanisms of Parkin mitochondrial translocation (a key consideration in mitophagy activation) and therapeutic implications of mitophagy in liver disease. DNA repair and other functions of Parkin beyond mitophagy are also briefly discussed. The paper additionally shows original data from the authors’ current research indicating enhanced hepatic mitophagy in ethanol-treated rats (ETRs), which is associated with Parkin mitochondrial translocation triggered by oxidative mitochondrial DNA damage. Natural or pharmaceutical products that may trigger Parkin mitochondrial translocation in hepatocytes and/or suppress repressors of such translocation could be a potential therapeutic target in alcoholic and non-alcoholic fatty liver disease